Application of adaptive neuro-fuzzy inference systems (ANFIS) to delineate estradiol, glutathione and homocysteine interactions. (August 2017) - Mohan, Iyyapu Krishna; Khan, Siraj Ahmed; Jacob, Rachel; Sushma Chander, Nooguri; Hussain, Tajamul; Alrokayan, Salman A.; Radha Rama Devi, Akella; Naushad, Shaik Mohammad
Summary: The rationale of the current study was to elucidate the contributing factors for the gender-based differences in total plasma homocysteine levels. A total of 413 subjects comprising of 293 men and 120 women were enrolled for the study. Chemiluminescence technology for vitamin B12, folate and total plasma homocysteine; ELISA for estradiol and 8-oxo-2-deoxyguanosine; Ellman's method for total glutathione; and PCR-RFLP analysis for the detection of methylene tetrahydrofolate reductase (MTHFR) C677T polymorphism were employed. No statistically significant differences were observed between the men and women in the distribution of age (p = 0.82), vitamin B12 (p = 0.23), folate (p = 0.36) and MTHFR C677T polymorphism (p = 0.35). However, the total plasma homocysteine levels were higher in men compared to women (28.4 ± 17.9 vs. 20.6 ± 13.6 μmol/L, p < 0.0001). In order to explain this gender differences in homocysteine, adaptive neuro-fuzzy inference systems (ANFIS) were developed to understand trivariate interactions among estradiol, glutathione and homocysteine. In the presence of adequate estradiol levels, inverse association was observed between glutathione and homocysteine. This association is lost when estradiol levels were inadequate. Estradiol was found to quench homocysteine mediated oxidative DNA damage. Irrespective of gender, combined deficiency of vitamin B12 and folate showed positive association with hyperhomocysteinemia and vice versa. Homocysteine reduction in response to vitamin status varied according to gender with men responding to folate and women responding to B12 . To conclude, gender-differences in homocysteine are attributable estradiol mediated lowering of homocysteine that prevents inactivation of glutathione mediated oxidative defense in women.